Analisis Etos Kerja Pemulung Dalam Meningkatkan Kualitas Hidup di Kecamatan Tikung Lamongan (Study Pemulung Muslim di Desa Jatirejo Kecamatan Tikung Lamongan) - Mahmudah, Henny (Jurnal Ekonomi dan Bisnis Islam, 2015)
This study aims to determine how much influence the Implementation of the Work Ethic In Improving Quality of Life Scavenger Muslim village, hamlet Jatirejo Mask District of Tikung Lamongan. Subyek research is Scavengers Muslims in the village Jatirejo Ticking subdistrict in Lamongan some 50 people. The data collection method using a questionnaire. Methods of analysis using logistic regression models. The results showed that the implementation of the work ethic of individual Muslims who mostly have a high work ethic can increase its revenue, so their quality of life can be improved. In this case can be seen from the quality of life Nagelkerke R Square of 0.551, this means 55.1% of the variable quality of life can be explained by the variable Work Ethic, while the value of R Square Negelkerke revenue of 0.552, this means that 55.2% Income variables can explained by the variable Work Ethics. There is a strong relationship between the two that the higher a persons work ethic, the higher the level of quality of life and the lower the persons work ethic the lower level of the quality of life it also affect the level of income.Â Keyword :Â work ethic, quality of life, scavengers